The use of eye tracking glasses in basketball shooting: a systematic review - Marques, R.; Martins, F.; Mendes, R.; Silva, M. C. E.; Dias, G. (Journal of Physical Education and Sport, 2018)
Sports performance is related to cognitive processes that precede the motor task to be developed. In this way, the coupling between visual information and motor behavior has a major importance in filtering the visual information, necessary to the accomplishment of the motor task to be executed, ignoring `accessory` stimuli. In this field, this essay has the goal of achieving a systematic review about past studies in the context of basketball shooting. We bring to you some evidence that support the applicability and efficiency of Eye Tracking Glasses systems in the analysis of visual attention in basketball shooting, emphasizing the concept of Quiet Eye, interconnected with anxiety and occlusion of vision. The results of the studies demonstrate the importance of the use of Eye Tracking Glasses for the evaluation/intervention in the process of visual attention training related to efficiency in shooting.